2020
DOI: 10.1101/2020.10.12.20210468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Treatment Outcomes Matter Most? A Q-study of Outcome Priority Profiles Among Youth with Lived Experience of Depression

Abstract: Objective: Over the past years, interest in youth perspectives on what constitutes an important outcome in the treatment of depression has been growing, but limited attention has been given to heterogeneity in outcome priorities and minority viewpoints. These are important to consider for person-centered outcome tracking in clinical practice, or when conducting clinical trials targeting specific populations. This study used Q-methodology to identify outcome priority profiles amongst youths with lived experienc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Our findings, whereby youth place a strong emphasis on learning to cope with anxiety and depression, are in line with existing qualitative research about young people’s treatment outcome priorities suggesting that youth assign similar levels of importance to learning to cope and self‐manage, as they do to symptom reduction (Krause, Edbrooke‐Childs, Edbrooke‐Childs, Bear, Calderón, & Wolpert, 2020; Krause, Midgley, Midgley, Edbrooke‐Childs, & Wolpert, 2020b). Yet, learning to cope is rarely an outcome of interest in treatment trials for youth depression (Krause, Bear, Edbrooke‐Childs, & Wolpert, 2019) and anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings, whereby youth place a strong emphasis on learning to cope with anxiety and depression, are in line with existing qualitative research about young people’s treatment outcome priorities suggesting that youth assign similar levels of importance to learning to cope and self‐manage, as they do to symptom reduction (Krause, Edbrooke‐Childs, Edbrooke‐Childs, Bear, Calderón, & Wolpert, 2020; Krause, Midgley, Midgley, Edbrooke‐Childs, & Wolpert, 2020b). Yet, learning to cope is rarely an outcome of interest in treatment trials for youth depression (Krause, Bear, Edbrooke‐Childs, & Wolpert, 2019) and anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…Improvements in mood and capacity for hedonia were a priority for all participants. However other outcomes such as learning coping skills, processing experiences, and functioning were important to differing degrees across profiles (Krause et al, 2020). Tailoring assessment using I-PROMs may contribute to the enhancement of treatment goals agreement (e.g., Sales et al, 2019), leading to the development of the therapeutic alliance (Bordin, 1979).…”
Section: Clinical Utilitymentioning
confidence: 99%
“…Research indicates that patients, even with the same diagnosis, may have very different expectations of therapy (Grosse & Grawe, 2002; Rajkarnikar, 2009). For instance, Krause et al (2020) found different outcome priority profiles for young people with experience of depression. Improvements in mood and capacity for hedonia were a priority for all participants.…”
Section: I‐proms In Psychological Therapies: a Narrative Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Historical analysis by McPherson and Armstrong (2021 ) has demonstrated that the concept of depression embodied in these measures has become narrower over time. Other studies have analysed qualitative evidence around how clients, their family members and therapists decide whether therapy has had an effect on depression and has found that these stakeholders make use of a much wider set of outcome criteria than those deployed in research studies ( Catchpole, 2020 ; Chevance et al, 2020 ; De Smet et al, 2020 ; Krause et al, 2020a , b ). Research into the experience of depression in everyday life has found that lay people possess complex and highly differentiated discourses and frameworks for making sense of recovery from depression ( Hänninen and Valkonen, 2019 ; Llewellyn-Beardsley et al, 2019 ; Bear et al, 2021 ), including a range of possible pathways to change ( Valkonen et al, 2011 ).…”
Section: Pluralistically Oriented Therapy Research: Illustrative Case Examplesmentioning
confidence: 99%